Electrical resistivity of Acacia and Eucalyptus wood chars - Kumar M.; Gupta R.C. (My University, 2025)
Electrical resistivity of Acacia and Eucalyptus wood chars, produced under different carbonization conditions, were measured using a two-probe technique. The results have shown that the final carbonization temperature is the most important factor because of its strong influence on the wood char resistivity. The electrical resistivity of these wood chars decreased drastically on increasing the carbonization temperature up to about 800 °C followed by a slight decrease with further rise of temperature up to 1200 °C. The wood species and increase in soaking time at carbonization temperatures of 800 and 1000 °C also influenced the char resistivity. It is hoped that the electrical resistivity values of wood chars can be used to determine their preparation temperature and to have a better control of the operation of electrosmelting furnaces using wood char as reductant. © 1993 Chapman & Hall.